Peningkatkan Hasil Belajar Bahasa Indonesia dengan Pendekatan Interaksi Edukatif Siswa Kelas VI SD Negeri 008 Pulau Lancang Kecamatan Benai Kabupaten Kuantan Singingi - Idawati, Idawati (GERAM: Gerakan Aktif Menulis, 2019)
The purpose of this study was to improve the learning outcomes of Indonesian language by using experiential learning models atsixth grade students of SD Negeri 008 Pulau Lancang, Benai District, Kuantan Singingi Regency. This research was conducted based on student learning activities in the Indonesian learning process is still low so as to produce learning does not meet the KKM which has been set by the school which is 70. Furthermore, this research was conducted in two cycles. Each cycle consists of four sides, namely planning, implementation, observation and reflection. To collect research data used a collection sheet that was filled by observers and learning outcomes tests given at the end of the cycle. Student learning activity data was analyzed by the number and percentage of students involved in each meeting. The improvement of learning outcomes can be seen from the number of students who completed at the end of the cycle. The results showed that learning activities and student learning outcomes improved after being implemented in the first cycle of students who achieved excellent grades from 12 students only 2 (17%), both 3 people (25%), sufficient categories of 2 people (17%) and at there are less categories of 5 students (42%) while in the second cycle increased to 8 students (67%) has found a very good category and 4 students (33%) in the good category that meant 100% of students have finished. Based on the result of the research, it can be concluded that the application of the educative learning model can improve the learning outcomes of Indonesian language of sixth grade students at SD Negeri 008 Pulau Lancang.